2023
DOI: 10.1111/jan.15613
|View full text |Cite
|
Sign up to set email alerts
|

Community empowerment: A concept analysis

Abstract: Aim To report an analysis of the concept of community empowerment. Design Concept analysis. Data Sources Literature published in the CINAHL, PubMed, Scopus and Medline electronic databases from 2016 to 2022 were systematically searched from 30 July to 1 October 2022. Method The amended guideline from Walker and Avant's approach (2011) to concept analysis was performed in nine stages: choosing a concept, determining the purpose of analysis, identifying definitions of the concept, defining attributes, identifyin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 32 publications
0
1
0
Order By: Relevance
“…Functional analysis grids and matrices are carried out as needed for each actor, category of actor, and organization, and they support the planning (see File S1 ). At each step, at least one representative from each category of stakeholders participates in the planning, which already constitutes an intervention in itself [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…Functional analysis grids and matrices are carried out as needed for each actor, category of actor, and organization, and they support the planning (see File S1 ). At each step, at least one representative from each category of stakeholders participates in the planning, which already constitutes an intervention in itself [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…Women empowerment is regarded as instrumental for enhancing infant and young child feeding among other things [ 39 ]. On the other hand, other studies have shown a need to empower communities as a whole to enable community members to define and make healthy dietary and lifestyle choices that will help them to improve their overall health status [ 27 ]. This study suggests that strategies should be designed to empower both parents collaboratively, fostering a sense of community and shared responsibility.…”
Section: Discussionmentioning
confidence: 99%
“…All of them can act together to address the persistent malnutrition epidemic. Kruahong et al [ 27 ] argued that a systems approach leads to system-thinking particularly in identifying how different systems can influence the risk factors for childhood malnutrition and enforce integrated strategies to prevent all forms of malnutrition. The systems approach guided the analysis and discussion of the key findings in this paper, because it allowed the researchers to explore various sectors (systems) at different levels (i.e., national-, regional- and lower-level) and assess how various sectoral strategies can work together towards addressing the malnutrition problem among under-fives in Tanzania.…”
Section: Introductionmentioning
confidence: 99%
“…Pemberdayaan masyarakat merupakan suatu proses yang bertujuan untuk meningkatkan kemampuan, pengetahuan, dan sumber daya individu dan masyarakat untuk mengendalikan pembangunannya (Kruahong et al, 2023). Dengan memberdayakan keluarga pemulung dan komunitasnya, siklus kemiskinan, eksklusi, dan terbatasnya peluang dapat diputus.…”
Section: Pendahuluanunclassified